Power enterprises-oriented carbon footprint verification system using edge computing and blockchain - Xue, Jizheng; Xu, YouRui; Yang, Yun (Frontiers in Energy Research, 2023)
The purpose is to study the Carbon Footprint (CF) verification system of power enterprises, promote the Low-Carbon Economy (LCE) in the power industry, and improve resource utilization during Energy Conservation and Emission Reduction (ECER). The Carbon Dioxide Emission (CDE) of power enterprises is explored based on the CF. First, Edge Computing (EC) is adopted to calculate the direct Carbon Dioxide Emission (CDE) of the Chinese power industry from 2005 to 2020 based on energy input. The direct CDE and the changing trend are analyzed. On this basis, Blockchain Technology (BCT) is employed to quantify the indirect CDEs of power enterprises’ energy consumption. A comprehensive analysis is made of the changing trend and circulation of the total CF of power enterprises based on the direct and indirect CDEs. The data show that the proportion of direct and indirect CDEs in total CF gradually decreases and increases. The results show that the power industry should increase the proportion of clean power in the power industry, control the CDEs from the source, and improve energy utilization to optimize the CF verification.